The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/md.0000000000005312
|View full text |Cite|
|
Sign up to set email alerts
|

Increased risk of depression in patients with acquired sensory hearing loss

Abstract: Acquired sensory hearing loss (SHL) is suggested to be associated with depression. However, some studies have reported conflicting results. Our study investigated the relationship between the prevalence of SHL and the incidence of depression over 12 years of follow-up by using data from the Taiwan National Health Insurance Research Database (NHIRD). We sought to determine the association between SHL and subsequent development of depression and discuss the pathophysiological mechanism underlying the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
65
4
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 32 publications
9
65
4
3
Order By: Relevance
“…Although depression does not have a direct effect on hearing, we should not overlook it because severe HL increases the risk of depression. 22,23 To this date, there has been no study indicating an association between fatty liver and hearing, and this was the same with our study. On the other hand, a case-control study suggested that patients with osteoporosis had a higher incidence of sensorineural HL, although there was a statistically significant age difference between the osteoporosis and control groups in the study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although depression does not have a direct effect on hearing, we should not overlook it because severe HL increases the risk of depression. 22,23 To this date, there has been no study indicating an association between fatty liver and hearing, and this was the same with our study. On the other hand, a case-control study suggested that patients with osteoporosis had a higher incidence of sensorineural HL, although there was a statistically significant age difference between the osteoporosis and control groups in the study.…”
Section: Discussionsupporting
confidence: 91%
“…In 112 subjects with depressive disorder, no difference in threshold changes was observed. Although depression does not have a direct effect on hearing, we should not overlook it because severe HL increases the risk of depression . To this date, there has been no study indicating an association between fatty liver and hearing, and this was the same with our study.…”
Section: Discussionsupporting
confidence: 82%
“…Although an association between HL and incident MDD has been reported previously, we did not find an association with MDD. Differences in findings might be explained by the older mean age of our sample, with some evidence suggesting a stronger relationship between HL and depression in younger ages .…”
Section: Discussioncontrasting
confidence: 90%
“…A Taiwanese study showed that over 12 years, HL was associated with increased incidence of depression relative to matched controls. 20 Concomitantly, an increased rate of depression symptoms following the onset of HL has also been observed. 21 Conversely, in a Dutch cohort, no relationship between HL and depression was found, although HL was associated with increased loneliness amongst men.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation